Car ownership and the distributional and environmental policies to reduce driving behavior - Miguel Angel Tovar Rea\~nos (The Economic and Social Research Institute (ESRI), 2020)
Using the EASI demand system and Irish data, it is found that additional carbon taxation is not as regressive as previously found, when the externality cost associated with driving is included in the metric of the tax incidence. This result is in contrast with the existing literature. Affluent households are found to have the largest externality costs and the largest average emissions per kilometer. Based on estimated cross price elasticities between public and private transportation it is found that for low income households, these commodities are complementary and substitutes for high-income levels. While subsidies for public transit can reduce emissions and the demand for private transportation, they are found to be regressive. A lump-sum transfer is found to perform better at compensating households after the carbon tax. However, it reduces the carbon savings by 1%.
Keywords: 330; Household energy demand; energy taxes; microsimulation; private transportation